2010
DOI: 10.1182/blood-2009-08-238543
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cell–derived type I interferon is crucial for the adjuvant activity of Toll-like receptor 7 agonists

Abstract: There is a high demand for the development of adjuvants that induce cytotoxic T lymphocytes, which are crucial for the elimination of intracellular pathogens and tumor cells. Toll-like receptor (TLR) agonists are prime candidates to fulfill this role because they induce innate immune activation and promote adaptive immune responses. The successful application of the TLR7 agonist R837 for treatment of basal cell carcinoma shows the potential for exploiting this pathway in tumor immunotherapy. Imidazoquinolines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 47 publications
(72 reference statements)
7
84
0
Order By: Relevance
“…Interestingly, a new cell population of CD11c + myeloid DCs endowed with tumoricidal potential was identified in these lesions [25]. The relevance of PDCs in cancer immunosurveillance has been recently shown in mice [68,69], where TLR9-activated PDCs lead to the regression of subcutaneous B16 melanoma tumors, by orchestrating the sequential activation of NK cells, MDCs and CD8 + T cells. The characterization of PDCs has been performed in a variety of human neoplasms [54,[70][71][72].…”
Section: Reviewmentioning
confidence: 98%
“…Interestingly, a new cell population of CD11c + myeloid DCs endowed with tumoricidal potential was identified in these lesions [25]. The relevance of PDCs in cancer immunosurveillance has been recently shown in mice [68,69], where TLR9-activated PDCs lead to the regression of subcutaneous B16 melanoma tumors, by orchestrating the sequential activation of NK cells, MDCs and CD8 + T cells. The characterization of PDCs has been performed in a variety of human neoplasms [54,[70][71][72].…”
Section: Reviewmentioning
confidence: 98%
“…Recently, Rajagopal et al (22) and Wei et al (23) have demonstrated that other TLR7 ligands, such as a 21-mer of polyuridylic acid (polyUs21) and influenza-infected cell lines, respectively, can enhance cross-priming in DCs, generating strong cytotoxic immune responses. However, the molecular mechanisms underlying the stimulatory effect of TLR ligands on cross-presentation are not fully resolved.…”
Section: Tlr7 Triggering With Polyuridylic Acid Promotes Cross-presenmentioning
confidence: 99%
“…The optimal ratio of polyU to DOTAP for complex formation was determined by dose titration (data not shown). It has been established that immunization with some TLR7 ligands, such as R848 (17), synthetic RNA oligonucleotides (35,36), influenza-infected allogeneic cell lines (23), or polyUs21 (22), led to potent CTL responses. To evaluate whether polyU is capable of acting as adjuvant for CTL response, mice were i.v.…”
Section: Polyu Induces a Cd8 + T Cell-mediated Cytotoxic Response In mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, TLR7-mediated B cell proliferation, cytokine production, and costimulatory molecule expression are defective in IFNAR 2/2 mice (14). Many synthetic TLR7 ligands are currently under investigation as vaccine adjuvants (15) and antitumor agents (16), and type I IFN also enhances adjuvant activity of such ligands (17).…”
mentioning
confidence: 99%